INCREASING KNOWLEDGE OF PREGNANT WOMEN ABOUT DANGER SIGNS DURING PREGNANCY - Margaretha Manungkalit, Eviyani; Kartiko Kusumo Wardani, Dyah Woro; Suhaid, Dewi Novitasari; Ida Pratiwi, Agustina; Panselina Widowati, Lorensia; Suci Dwi Aningsih, Baharika; Sri Artina Dewi, Ni Nyoman; Leoni Irawan, Yetty (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Premature membrane rupture, extreme stomach pain, severe headaches, and bleeding are all warning signs of pregnancy. impacts such as miscarriage, early pregnancy, fetal discomfort, and pregnancy-related toxicity that could affect the mother's health and the safety of the unborn child. If the mother and family are aware of the risk indicators of pregnancy and take prompt action to overcome them, complications can be prevented and addressed early. In light of this, it is crucial for moms to be aware of the pregnancy's risk indicators, such as bleeding and an early rupture of the membranes, through education in order to prevent difficulties and assist mothers in recognizing their pregnancy. The technique employed in this activity is to coach participants about pregnancy-hazard symptoms. Online games are played with expectant mothers and their families. Following the counseling, there was an improvement in knowledge of the pregnancy danger signals, going from 76 (pre-test) to 97 (post-test).